Cardiovascular Autonomic Regulation in Response to Orthostatic Stress with Parkinson's Disease - Case Report - Zawadka, Monika; Zalewski, Paweł; Klawe, Jacek J.; Tafil-Klawe, Małgorzata; Pawlak, Joanna; Kunikowski, Krzysztof; Bitner, Anna (Medical and Biological Sciences, 2012)
Background and purpose. The most commonly reported disturbances of ANS function in PD are cardiovascular symptoms. The aim of the study was to evaluate hemodynamic parameters and heart rate variability in response to orthostatic stress in patient with Parkinson's disease. Material and methods. In our study we used Task Force Monitor System designed for non-invasive measurement of cardiovascular system and assessment of functional autonomic nervous system. The device measures and calculates hemodynamic parameters such as: cardiac output (CO), cardiac index (CI) stroke volume (SV), heart rate (HR), RR-Interval (RRI), Total Peripheral Resistance (TPR) and systolic (sBP), diastolic (dBP), mean (mBP) blood pressures [25;26]. Estimated parameters of heart rate variability (HRV) spectral analysis: LFnu-RRI, HFnu-RRI, LF-RRI, HF-RRI, PSD-RRI, LF/HF. Results and conclusions. Parkinson's disease causes autonomic dysfunctions leading to abnormalities in cardiovascular regulation. Dysautonomia in Parkinson's disease patient is demonstrated by decreased heart rate variability (HRV). The head up tilt test revealed a decreased LF/HF ratio and sympathovagal balance disorders.